ANALYSIS OF STRESS AT THE JUNCTION BETWEEN PRESSURE VESSEL AND NOSEL: THE COMPARISON BETWEEN WRC107 AND FINITE ELEMENT METHOD - HANAFIA (NIM : 13104142); Pembimbing : Dr. Rachman Setiawan, FARID
Pressure vessel is very important in application such as in chemical industry, pertrochemical, oil, and nuclear. The rapture of prssure vessel has a potential to cause physical injury and property damage. In pressure vessel design, the load such as pressure, temperature, wind, piping load etc. can be derived from analytical method or standard. WRC107 “Local Stress in Spherical and Cylindrical Shells due to External Loadings” is used to evaluate local stress at the junction between pressure vessel and nosel. In this research, parameters and the stress resulted from WRC107 method are compared to the solution of finite element method. PVElite is used to calculate the WRC107 stress and nondimensional membran force and bending momen. ANSYS 11 is used to calculate the finite element method result. The value of stress and nondimensional curves that are obtained by finite element sofware, ANSYS 11, show some similarities and differencies. The curves are obtained by finite element method mostly lower than curves in WRC107. And the others are nearly have the same level and higher. From 33 cases that are modeled and applied external loadings (radial force, moment, and shear force) show that WRC107 are more conservative to calculate the stress at one of locations of Au or Bu. But it may be will obtain lower stress value at one of locations of Cu or Du. And the differences occur between the result of finite element method and WRC107 calculation in analyzing the shear stress at the four locations. By finite element method, the differencies of shear stress at upper and lower location, and so the shear stress at A and B diferent from the shear stress at C and D.